Dear Emmie Blue - Louis, Lia (Emily Bestler Books, Atria, 2020)
"A novel about teenager Emmie Blue, who releases a balloon with her email address and a big secret into the sky, only to fall head-over-heels for the boy who finds it; now, fourteen years later, the one thing Emmie has been counting on is gone for good, and everything she planned is up in the air"--